2019
DOI: 10.1177/0284185119861898
|View full text |Cite
|
Sign up to set email alerts
|

Reduced gray matter volume in patients with retinal detachment: evidence from a voxel-based morphometry study

Abstract: Background We know little about the pathogenesis and diagnosis of retinal detachment. Purpose To assess spontaneous changes in the cerebral cortex of patients with retinal detachment using voxel-based morphometry and to explore the relationship between retinal detachment and clinical behavioral performance. Material and Methods Patients (14 men, 6 women; average age = 49.15 ± 10.32 years) with rhegmatogenous retinal detachment (duration of 24.05 ± 19.61 days) and 20 matched healthy controls were recruited. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The superior and middle temporal gyri are thought to specialize in processing dorsal signals along the visual pathway [49]. Previous studies have observed abnormalities in the superior temporal gyrus in specific ophthalmopathy, including but not limited to optic neuritis [50], diabetic retinopathy [51], comitant strabismus [18], and retinal detachment [23]. In this study, the decrease in GMV in the superior temporal gyrus may indicate atrophy of temporal retinal fibers in NVG patients [29] (Table 4).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The superior and middle temporal gyri are thought to specialize in processing dorsal signals along the visual pathway [49]. Previous studies have observed abnormalities in the superior temporal gyrus in specific ophthalmopathy, including but not limited to optic neuritis [50], diabetic retinopathy [51], comitant strabismus [18], and retinal detachment [23]. In this study, the decrease in GMV in the superior temporal gyrus may indicate atrophy of temporal retinal fibers in NVG patients [29] (Table 4).…”
Section: Discussionmentioning
confidence: 55%
“…At present, in addition to cognitive diseases, VBM has been applied in ophthalmic diseases, including optic neuromyelitis [15], advanced monocular blindness [16], amblyopia [17], comitant strabismus [18], glaucoma [19], and acute eye pain [20] (Table 1, Ref. [15,16,18,[20][21][22][23]).…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to study the pathology of trigeminal neuralgia, senile dementia, mild cognitive impairment, and motor neuron diseases [ 12 14 ]. In ophthalmology, it has also been used to increase understanding of optic neuritis, retinal detachment, acute eye pain, advanced monocular blindness [ 15 18 ], and nAMD. It offers a powerful method of elucidating the pathological mechanisms of those diseases, and monitoring the course of their progression.…”
Section: Introductionmentioning
confidence: 99%
“…Voxel-based morphometry (VBM) is another MRI technique and is used to assess structural compositions of individual voxels in whole brain volume, gray matter volume (GMV) and white matter volume ( Ashburner and Friston, 2000 ). In recent years, the VBM approach has been used in ocular diseases such as retinal detachment ( Li et al, 2020 ), proliferative diabetic retinopathy ( Xiao et al, 2021 ), and acute eye pain ( Lan et al, 2019 ). A previous study found that severely obese individuals had increased risk of cognitive impairment such as Alzheimer’s disease, a neurodegenerative disorder caused by reduced GMV ( Gustafson et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%